The Development of IFRS Implementation Index and its Effect on Corporate Values in Indonesia in 2015 - Ahalik, Ahalik; Murwaningsari, Etty; Mayangsari, Sekar; Aryati, Titik (Journal of Accounting, Business and Finance Research, 2019)
Indonesia has adopted the latest international accounting standards, namely IFRS (International Financial Reporting Standard) since January 1, 2012, thus accounting standards in Indonesia called financial accounting standard statements (PSAK) have been based on IFRS, where before Indonesia refers to American accounting standards (US GAAP - United States Generally Accepted Accounting Principle. The adoption of the IFRS is one of Indonesia’s commitments as a G20 country. G20 countries consist of developed and developing countries in the world which represent 2/3 of the world’s population and 75% of world trade, thus, it can be said that IFRS have become global standards. This research was conducted to determine the development of the IFRS implementation index and its influence on the value of companies in Indonesia. The research method uses multiple regression, with purposive sampling method as many as 45 companies that have used PSAK. The results of the study show that the IFRS implementation variable has a negative and significant relationship to the value of the company through economic value added. This shows the ability of corporate value through economic value added does not have an impact on IFRS implementation in companies in Indonesia.